Penerapan Arsitektur Tropis pada Rest Area di Katoi Kabupaten Kolaka Utara - Fajar Fajar; Ilham Ilham; Nahdatunnisa Nahdatunnisa (Arsitektur Universitas Muhammadiyah Kendari, 2021)
Rest area in Katoi North Kolaka Regency is a stopover / resting place. Designing a rest area that can adequate the needs of road users who travel far, with the aim as a means of accommodation that can meet the needs. When resting and can be a means of recreation for rest areausers. The approach method used in this research is a descriptive analysis method, namely by collecting, describing, compiling and analyzing data so that a planning and design program approach is obtained for further use in the preparation of space programs and the basic concepts of planning and design. Discussion produces a concept of design reference, namely macro concept, and micro concept. Macro concepts discuss references in determining location, managing site / site, circulation, basic shape and appearance of buildings, and the arrangement of outdoor spaces. While the micro concept discusses the reference on the needs that can support functions in the building, including facilities and infrastructure in the rest areabuilding. With the planning and design of rest areas, it is expected to be an adequate facility for Trans Sulawesi road as a means of accommodation for road users, so as to reduce the accident rate. The application of tropical architectural themes in rest areas is expected to overcome the problems posed by the climate. Tropical architecture can provide solutions to buildings through natural lighting and natural conditioning, so that comfort can be felt for its users.